Competence-based Operation in Human Processes of Companies - Tóthné Kiss, Anett (Theory, Methodology, Practice – Review of Business and Management, 2012)
they should become more efficient and more modern. Nowadays, a good product or service and a lean organization is not a guarantee of success. In this harsh competition continuous innovation is more and more important to change over and over again and thus develop our operation and the processes which create the value. In business processes the human factor has always been important; however, nowadays there is a growing amount of research about how to contribute to the more efficient operation of companies. The structural utilization of the competence research results and competence-based human resource management is a significant policy.